Monomial Curves in Afinne Space and their Associated Prime Ideals with Six Generators as Set-Theoretic Complete Intersections - Michaela Holesova (Communications - Scientific letters of the University of Zilina, 2014)
The paper deals with the problem of the expression of associated prime ideals of monomial curves in the affine space A4 as set-theoretic complete intersections. We describe some associated prime ideals, a minimal generating set of which has six elements and we prove that these ideals are set-theoretic complete intersections. Corresponding monomial curves are intersections of three hypersurfaces and we find the equations of these hypersurfaces.